2016
DOI: 10.1590/s0100-736x2016001300015
|View full text |Cite
|
Sign up to set email alerts
|

Starvation and refeeding in rats: effect on some parameters of energy metabolism and electrolytes and changes of hepatic tissue

Abstract: Regarding the importance of starvation and refeeding and the occurrence of refeeding syndrome in various conditions, the present study was conducted to investigate the effects of refeeding on some parameters of energy metabolism and electrolytes and changes of hepatic tissue in male Wistar rats. Fifty-seven rats were divided into six groups, having 6 to 11 rats. Food was provided ad-libitum until three months and then the first group was considered without starvation (day 0). Other rats were fasted for two wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Although this amount of energy might be insufficient for RFS development, it is conceivable that our glucose dosage was sufficient to promote refeeding hypophosphatemia in light of previous reports of the effects of reintroduction of carbohydrates in this syndrome (22). Some reports have demonstrated RFS in animals ; however, symptoms appeared after several days (23,24). Because of the direct infusion of glucose solution via intravenous administration, we were able to observe hypophosphatemia within one day.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Although this amount of energy might be insufficient for RFS development, it is conceivable that our glucose dosage was sufficient to promote refeeding hypophosphatemia in light of previous reports of the effects of reintroduction of carbohydrates in this syndrome (22). Some reports have demonstrated RFS in animals ; however, symptoms appeared after several days (23,24). Because of the direct infusion of glucose solution via intravenous administration, we were able to observe hypophosphatemia within one day.…”
Section: Discussionmentioning
confidence: 54%
“…Since insulin activates ATPase (25), increasing insulin concentrations might stimulate Pi consumption for ATP generation, which is essential for energy production. Namazi et al reported that refeeding after starvation decreased serum K and Pi concentrations, increased insulin levels and altered the hepatic histopathology in rats (24). The effect of changes in glucose or lipid metabolism on liver tissues may be associated with insulin-stimulated Pi consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increase in the serum SGPT observed in refeeding animals is a consequence of a number of liver disorders including hydropic changes as well as fatty liver already described. A longer-term study found only vacuoles after starvation and refeeding in the tissues of animals, and the severity of lesions gradually decreased during refeeding [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…For 2 weeks, rat chow was withheld from a group of rats to test the effect of starving (Namazi et al, 2016 ). During the protracted hunger, none of the rats died.…”
Section: Methodsmentioning
confidence: 99%